Identification of Datura innoxia as a potential source of antimycobacterial components - Khan, Sajjad Ahmed; Rather, Muzafar Ahmad; Sheeraz Ahmad, Muhammad; Jia, Ziyi; Baughn, Anthony D.; Iqbal, Sajid; Qadir, Syed Mehmood; Tahseen, Sabira; Khan, Muhammad Umer; Villalta, Peter W.; Shier, W. Thomas (Frontiers in Microbiology, 2025)
Datura innoxia is a medicinal plant from the Solanaceae family, having medicinal properties and some toxic effects. It is widely distributed across Asia, Africa, Europe, the Americas, and other tropical and subtropical regions, where it is utilized by local pharmaceutical industries. In this study, bioassay-guided fractionation and LC-MS/MS analysis were used for the identification of secondary metabolites with anti-tuberculosis activity in methanolic leaf extracts of D. innoxia. Bioassay-guided fractionation was conducted using normal and reverse phase column chromatography, and the fractions were assayed for antituberculosis activity in vitro by serial dilution in Mycobacterium tuberculosis H37Ra cultures. The structures of known secondary metabolites in the purified extracts were identified using LC-ESI-MS/MS mass spectroscopy. A purified fraction of the methanolic extract of D. innoxia leaves inhibited M. tuberculosis growth at concentrations as low as 25 μg/mL. Metabolic profiling with LC-ESI-MS/MS enabled the identification of the purified extract of 16 known metabolites, including loliolide, scopolamine, kuromanin, isoquercitrin, moupinamide, methyl isoquinoline-3-carboxylate, trans-3-Indoleacrylic acid, tyramine, (3β,5ξ,9ξ)-3,6,19-trihydroxyurs-12-en-28-oic acid, milbemycin A3 oxime, methyl jasmonate, nicotinamide, methyl ferulate, trifolin, 2-[(1S,2S,4aR,8aS)-1-hydroxy-4a-methyl-8-methylidene-decahydronaphthalen-2-yl]prop-2-enoic acid, and methyl 4-hydroxycinnamate. These results indicate that D. innoxia is a rich natural source of potential antitubercular secondary metabolites.